2011
DOI: 10.3345/kjp.2011.54.9.368
|View full text |Cite
|
Sign up to set email alerts
|

An update on necrotizing enterocolitis: pathogenesis and preventive strategies

Abstract: Necrotizing enterocolitis (NEC) is one of the most critical morbidities in preterm infants. The incidence of NEC is 7% in very-low-birth-weight infants, and its mortality is 15 to 30%. Infants who survive NEC have various complications, such as nosocomial infection, malnutrition, growth failure, bronchopulmonary dysplasia, retinopathy of prematurity, and neurodevelopmental delays. The most important etiology in the pathogenesis of NEC is structural and immunological intestinal immaturity. In preterm infants wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 54 publications
1
21
0
2
Order By: Relevance
“…Thirtyday post-operative mortality was 19 times greater among children with ASA scores 3 or above. Regarding necrotizing enterocolitis, which is known to be a life-threatening condition mainly related to immaturity and low birth weight [21][22][23] , our results were largely consistent with others that report post-operative high morbidity and mortality following surgery for this condition, given its progression to abdominal sepsis with multiorgan failure [24][25][26] . In the current study, necrotizing enterocolitis was found to be the leading primary cause of in-hospital mortality following neonatal surgery, accounting for 41% of all causes of 30-day post-operative mortality.…”
Section: Discussionsupporting
confidence: 91%
“…Thirtyday post-operative mortality was 19 times greater among children with ASA scores 3 or above. Regarding necrotizing enterocolitis, which is known to be a life-threatening condition mainly related to immaturity and low birth weight [21][22][23] , our results were largely consistent with others that report post-operative high morbidity and mortality following surgery for this condition, given its progression to abdominal sepsis with multiorgan failure [24][25][26] . In the current study, necrotizing enterocolitis was found to be the leading primary cause of in-hospital mortality following neonatal surgery, accounting for 41% of all causes of 30-day post-operative mortality.…”
Section: Discussionsupporting
confidence: 91%
“…In a prospective study, higher rates of alcohol consumption were found among Present Hedonistic and Past Negative individuals 34. Impulsive drinking and drug abuse were directly correlated with ADHD diagnosis in various studies 35,36. Individuals with a diagnosis of childhood ADHD and conduct disorder were found to be at much higher risk than controls for becoming “drug abusers” in adolescence 37…”
Section: Correspondence In Lifestyles Of Adhd and Present Hedonistic mentioning
confidence: 98%
“…Indeed, the protective role of maternal milk in NEC pathogenesis has been reported both in human [9] and animal studies [14,27]. These findings stimulated the search for various components of milk that might be responsible for protection against NEC.…”
Section: Discussionmentioning
confidence: 91%
“…Several potential preventive strategies have aimed at induction of gastrointestinal maturation in premature infants, however, none of them have led to consistently positive results [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%